Group early intervention eye movement desensitization and reprocessing therapy as a video-conference psychotherapy with frontline/emergency workers in response to the COVID-19 pandemic in the treatment of post-traumatic stress disorder and moral injury—An RCT study - Farrell, Derek; Moran, Johnny; Zat, Zeynep; Miller, Paul W.; Knibbs, Lorraine; Papanikolopoulos, Penny; Prattos, Tessa; McGowan, Iain; McLaughlin, Derek; Barron, Ian; Mattheß, Cordula; Kiernan, Matthew D. (Frontiers in Psychology, 2023)
Objective Frontline mental health, emergency, law enforcement, and social workers have faced unprecedented psychological distress in responding to the COVID-19 pandemic. The purpose of the RCT (Randomized Controls Trial) study was to investigate the effectiveness of a Group EMDR (Eye Movement Desensitization and Reprocessing) therapy (Group Traumatic Episode Protocol—GTEP) in the treatment of Post-Traumatic Stress Disorder (PTSD) and Moral Injury. The treatment focus is an early intervention, group trauma treatment, delivered remotely as video-conference psychotherapy (VCP). This early intervention used an intensive treatment delivery of 4x2h sessions over 1-week. Additionally, the group EMDR intervention utilized therapist rotation in treatment delivery. Methods The study’s design comprised a delayed (1-month) treatment intervention (control) versus an active group. Measurements included the International Trauma Questionnaire (ITQ), Generalized Anxiety Disorder Assessment (GAD-7), Patient Health Questionnaire (PHQ-9), Moral Injury Events Scale (MIES), and a Quality-of-Life psychometric (EQ-5D), tested at T0, T1: pre—treatment, T2: post-treatment, T3: 1-month follow-up (FU), T4: 3-month FU, and T5: 6-month FU. The Adverse Childhood Experiences – International version (ACEs), Benevolent Childhood Experience (BCEs) was ascertained at pre-treatment only. N = 85 completed the study. Results Results highlight a significant treatment effect within both active and control groups. Post Hoc comparisons of the ITQ demonstrated a significant difference between T1 pre (mean 36.8, SD 14.8) and T2 post (21.2, 15.1) (t11.58) = 15.68, p < 0.001). Further changes were also seen related to co-morbid factors. Post Hoc comparisons of the GAD-7 demonstrated significant difference between T1 pre (11.2, 4.91) and T2 post (6.49, 4.73) (t = 6.22) = 4.41, p < 0.001; with significant difference also with the PHQ-9 between T1 pre (11.7, 5.68) and T2 post (6.64, 5.79) (t = 6.30) = 3.95, p < 0.001, d = 0.71. The treatment effect occurred irrespective of either ACEs/BCEs during childhood. However, regarding Moral Injury, the MIES demonstrated no treatment effect between T1 pre and T5 6-month FU. The study’s findings discuss the impact of Group EMDR therapy delivered remotely as video-conference psychotherapy (VCP) and the benefits of including a therapist/rotation model as a means of treatment delivery. However, despite promising results suggesting a large treatment effect in the treatment of trauma and adverse memories, including co-morbid symptoms, research results yielded no treatment effect in frontline/emergency workers in addressing moral injury related to the COVID-19 pandemic. Conclusion The NICE (2018) guidance on PTSD highlighted the paucity of EMDR therapy research used as an early intervention. The primary rationale for this study was to address this critical issue. In summary, treatment results for group EMDR, delivered virtually, intensively, using therapist rotation are tentatively promising, however, the moral dimensions of trauma need consideration for future research, intervention development, and potential for further scalability. The data contributes to the emerging literature on early trauma interventions. Clinical Trial Registration:Clinicaltrials.gov, ISRCTN16933691.